The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12935-020-01591-3
|View full text |Cite
|
Sign up to set email alerts
|

BTG1 inhibits malignancy as a novel prognosis signature in endometrial carcinoma

Abstract: Background Endometrial carcinoma (EC) is one of the three major malignant tumors of the female reproductive system. In recent years, the incidence and mortality rate of EC have increased. B-cell translocation gene 1 (BTG1) is an anti-proliferation gene that regulates the occurrence and development of a variety of tumors, but there is no research regarding this gene in EC. Methods Based on The Cancer Genome Atlas (TCGA) database, we used a variety of bioinformatics tools and databases to explore the expressio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…Another study based on RNA-seq data reported that 542 patients had high RNF183 expression, which was associated with favorable overall survival and progression-free survival [48]. It was similar in the study by Li et al, where higher OS was noted in patients with high BTG1 expression [50]. In turn, high expression of HOXB9 and E2F3 correlated with a shorter survival time [51].…”
Section: Kaplan-meier Plotter Databasesupporting
confidence: 65%
See 4 more Smart Citations
“…Another study based on RNA-seq data reported that 542 patients had high RNF183 expression, which was associated with favorable overall survival and progression-free survival [48]. It was similar in the study by Li et al, where higher OS was noted in patients with high BTG1 expression [50]. In turn, high expression of HOXB9 and E2F3 correlated with a shorter survival time [51].…”
Section: Kaplan-meier Plotter Databasesupporting
confidence: 65%
“…In a recent endometrial cancer study, 581 TCGA tissue samples, including 546 EC samples and 35 normal endometrial samples, were used during analysis. Expression of TMEFF2 [47] and BTG anti-proliferation factor 1 (BTG1) [50] was lower in primary endometrial cancer compared to the healthy endometrium, while significant overexpression was noted for ring finger protein 183 (RNF183) [48]. In turn, the ZBTB7A expression was low in endometrial cancer tissues grouped according to cancer stage, age, and race compared to the control group [49].…”
Section: Ualcan Databasementioning
confidence: 97%
See 3 more Smart Citations